Statistical downscaling of rainfall under transitional climate in Limbang River Basin by using SDSM - Tahir, T. (Institute of Physics Publishing, 2018)
Climate change is a global phenomenon that has affected hundreds of people around the globe. In transitional climatic patterns, it is essential to compute the severity of rainfall in the regions prone to hydro-meteorological disasters. Therefore, the main aim of this study is to assess the severity of rainfall under three Representative Concentration Pathways (RCPs) from Global Climate Model data of CanESM2 in Limbang River basin. Furthermore, the objective is to check the capability of Statistical Downscaling Model (SDSM) in the tropical region. The historical data of nine weather stations were used for the period of 30 years (1976 - 2005) and Global Climate Model data of CanESM2 under RCPs of RCP2.6, RCP4.5 and RCP8.5 for the period of 2071-2100. The model was calibrated for the period of 1976-1995 and validated for the period of 1996-2005. After successful calibration and validation of SDSM, the future rainfall was simulated separately for all the three scenarios of RCPs. The obtained results have shown the values of R2 and RMSE for the model calibration and validation ranged between 0.58 - 0.86 and between 1.49 and 4.7, respectively for all stations. The obtained future rainfall data from 2071 - 2100 was then compared with the base period rainfall from 1976 - 2005. It was shown that under RCP2.6 scenario there will be an increase of 8.13, while 14.7 rise in the RCP4.5 scenario during the period of 2071- 2100. An abrupt increase of about 40.6 was observed under the robust scenario of RCP8.5. Therefore, it is concluded that future pattern of rainfall in Limbang River basin under all the scenarios is constantly increasing due to the climate change. Â© 2018 Published under licence by IOP Publishing Ltd.